How do you solve using gaussian elimination or gauss-jordan elimination, x+2y-z=-5x+2yz=5, 3x+2y+3z=-73x+2y+3z=7, 5x-y-2z=-305xy2z=30?

1 Answer

x=-5x=5
y=1y=1
z=2z=2

Explanation:

Gaussian Elimination or Gauss-Jordan elimination

[(1,2,-1,|,-5),(3,2,3,|,-7),(5,-1,-2,|,-30)]

[(1,2,-1,|,-5),(0,-4,6,|,8),(0,-11,3,|,-5)]

[(1,2,-1,|,-5),(0,-2,3,|,4),(0,-11,3,|,-5)]

[(1,2,-1,|,-5),(0,-2,3,|,4),(0,-1,-12,|,-25)]

[(1,2,-1,|,-5),(0,1,39,|,79),(0,-1,-12,|,-25)]

[(1,0,-79,|,-163),(0,1,39,|,79),(0,0,27,|,54)]

[(1,0,0,|,-5),(0,1,0,|,1),(0,0,1,|,2)]

x=-5
y=1
z=2

God bless....I hope the explanation is useful.